Drying kinetics and sensory characteristics of dehydrated pumpkin seeds (Cucurbita moschata) obtained by refractance window drying (2022)
ABSTRACT: The current importance of pumpkin (Cucurbita moschata) in national food security has progressively encouraged research on this fruit. This is how pumpkin seeds constitute a potential raw material to obtain dehydrated products for direct consumption. In this research, we compared the drying kinetics, effective diffusivity (Def) and sensory perception in a non-trained panel of dehydrated pumpkin seeds through refractance window drying (RW) and convective air drying (CA). RW drying was carried out in a laboratory-scale hydro-dryer and CA drying was carried out in a dryer with hot air circulation; both at 80 2 C. Sensory acceptability (appearance, aroma, taste and texture) was evaluated by an affective test on a hedonic scale from 1 to 5 with 60 panelists. The drying curves (MR vs t) were fitted to four kinetic models: Newton, Logarithmic, Page and Midilli et al. Def was determined by the second Fick’s Law solution. The best model for RW drying was logarithmic, and Def was 6.60 1010 m2/s (R2 1⁄4 0.9927); while for CA, it was Midilli et al., with the Def found through this method being 9.60 1010 m2/s (R2 1⁄4 0.9928). Dry seeds by RW obtained a general acceptance of 3.82, compared to 3.63 by CA. Results allow us to conclude that among the drying methods evaluated, there is not statistically significant differences, in terms of dehydration characteristics and sensory acceptability, constituting RW drying as an alternative method for obtaining dehydrate pumpkins seeds for direct consumption.